Early onset bioprosthetic tricuspid valve stenosis in a case with cardiac sarcoidosis: Pathological findings based on autopsy. Issue 4 (April 2021) - Hirata, Kazuhito; Tamaki, Yusuke; Yakabi, Chiaki; Ishiyama, Taku; Takahashi, Takanori; Wake, Minoru; Tengan, Toshiho; Mototake, Hidemitsu
Abstract: A 60-year-old woman with cardiac sarcoidosis developed recurrent and refractory right heart failure 26 months after tricuspid valve replacement. Echocardiography revealed thickened and immobile cusp with increased diastolic tricuspid gradient of 8–10 mmHg, consistent with bioprosthetic tricuspid stenosis (TS). Prolonged intravenous injection of dobutamine and carperitide, with intermittent intravenous furosemide, was necessary at multiple times. Despite treatment, the patient died of refractory right heart failure. The explanted tricuspid bioprosthesis on autopsy revealed marked pannus formation, resulting in stiff and immobile cusps while the same mitral bioprosthesis, which was implanted on the same day, was normal. Sarcoid granulomas were not present either in tricuspid or mitral bioprostheses. Chronic valve inflammation associated with prolonged use of intravenous drugs and multiple episodes of line-associated bacteremia may have caused early onset bioprosthetic TS. Learning objectives: 1 Early onset bioprosthetic tricuspid stenosis (TS) is rare. 2 Elevated jugular venous pulse and pan-diastolic rumble with the Rivero–Carvallo sign are keys to the diagnosis of TS which is confirmed using echocardiography. 3 Repeated episodes of bacteremia associated with prolonged infusion of intravenous drugs might have contributed to the development of early onset bioprosthetic TS.